1996
DOI: 10.1021/es950754r
|View full text |Cite
|
Sign up to set email alerts
|

Bioremediation of an Experimental Oil Spill on the Shoreline of Delaware Bay

Abstract: Even though oil loss was enhanced by nutrient addition, active bioremediation in the form of exogenous nutrient addition might not be appropriate in cases where background nutrient levels are already sufficiently high to support high intrinsic rates of hydrocarbon biodegradation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
210
5
5

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 373 publications
(240 citation statements)
references
References 23 publications
20
210
5
5
Order By: Relevance
“…The major threats to the American horseshoe crab (i.e., those stressors that could impact population viability and lead to regional or species extinction) are commercial harvest for bait, production of a biomedical product, and marine life specimens for research, education, and aquaria Davis et al 2006;Brockmann et al 2015), spawning habitat loss (Botton et al 1994;Jackson and Nordstrom 2009), pollution (Venosa et al 1996;Strobel and Brenowitz 1981;Botton and Itow 2009), bycatch (Gerhart 2007), impingement by coastal infrastructure (including power plants) and climate change (Loveland and Botton 2015). Also, an emerging threat is the importation of Asian species for use as bait in the whelk and eel fisheries in the Mid-Atlantic region with the associated risk of introduction of pathogens, parasites, and non-native species .…”
Section: Generalmentioning
confidence: 99%
“…The major threats to the American horseshoe crab (i.e., those stressors that could impact population viability and lead to regional or species extinction) are commercial harvest for bait, production of a biomedical product, and marine life specimens for research, education, and aquaria Davis et al 2006;Brockmann et al 2015), spawning habitat loss (Botton et al 1994;Jackson and Nordstrom 2009), pollution (Venosa et al 1996;Strobel and Brenowitz 1981;Botton and Itow 2009), bycatch (Gerhart 2007), impingement by coastal infrastructure (including power plants) and climate change (Loveland and Botton 2015). Also, an emerging threat is the importation of Asian species for use as bait in the whelk and eel fisheries in the Mid-Atlantic region with the associated risk of introduction of pathogens, parasites, and non-native species .…”
Section: Generalmentioning
confidence: 99%
“…Peng et al found that the degradation of alkane was more effective than that of aromatics compounds [55]. By contrast, other researchers separated petroleum degrading microorganism from the strains in marine sediments that could breakdown aromatics hydrocarbons effectively [71].…”
Section: Molecular Weight Of Petroleum Hydrocarbonsmentioning
confidence: 99%
“…Generally, the low-sulfur petroleum hydrocarbons could be easily degraded by some microorganism [33,66,71]. However, saturated hydrocarbon with higher proportion of sulfur still has a higher degradation rate than aromatic compounds [66].…”
Section: Some Petroleum Components Could Affect the Degradation Efficmentioning
confidence: 99%
“…Although we have noted that successful bioremediation can be achieved if nutrients were applied in a trench landward of a fine-textured beach, these beaches are characterized by a low hydraulic conductivity, which implies that the nutrients might not reach the bioremediation zone before the high tide occurs. Therefore it appears that application of the nutrients onto the beach surface at low tide [Venosa et al, 1996] is the best application strategy. A refinement on the method used by Venosa et al [1996] for coarse beaches would be to apply the nutrient solution intermittently on the beach surface to provide sufficient moisture for microbial growth.…”
Section: Effect On Bioremediationmentioning
confidence: 99%